Analysis Of Factors Affecting The Open Unemployment Rate In Sumatera And Java Islands 2015-2024 - Muhammad Naufal Akbar; Arif Darmawan; Arivina Ratih; Heru Wahyudi (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effects of education (average years of schooling), Information and Communication Technology (ICT) skills, Provincial Minimum Wage (UMP), and economic growth on the open unemployment rate (TPT) in Sumatera and Java Islands during the 2015–2024 period. The analytical method used is panel data regression with the Fixed Effect Model (FEM) approach. The results indicate that education and economic growth have a negative and significant effect on the unemployment rate, implying that improvements in these variables help reduce unemployment. Conversely, ICT has a positive and significant impact, suggesting potential job displacement due to labor force unpreparedness in facing digital transformation. Similarly, the UMP variable also has a positive effect, showing that wage increases without corresponding labor productivity may lead to higher unemployment. This study recommends policy strategies that enhance education quality, ICT-based workforce training, and inclusive economic development to effectively reduce unemployment rates.